2004
DOI: 10.1002/hep.20365
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study for differences among hepatitis B virus infections of genotypes A (subtypes Aa and Ae) and D †

Abstract: There are two subtypes of hepatitis B virus genotype A (HBV/A) and they are provisionally designated Aa ("a" standing for Africa/Asia) and Ae ("e" for Europe). In a case-control study, 78 HBV/Aa, 78HBV/Ae, and 78HBV/D carriers from several countries were compared. The prevalence of HBe antigen (HBeAg) in serum was significantly lower in carriers of HBV/Aa than in carriers of HBV/Ae (31% vs. 49%; P = .033), with a difference more obvious in the carriers aged 30 years or younger (34% vs. 67%; P = .029). HBV DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
147
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 140 publications
(169 citation statements)
references
References 49 publications
19
147
3
Order By: Relevance
“…These findings are consistent with the fact that genotype Aa, which often has T1862 as its wild-type sequence, continues to express HBeAg (25,27). Do mutations at nucleotides 1862, 1863, and 1869 just down regulate core protein expression?…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These findings are consistent with the fact that genotype Aa, which often has T1862 as its wild-type sequence, continues to express HBeAg (25,27). Do mutations at nucleotides 1862, 1863, and 1869 just down regulate core protein expression?…”
Section: Discussionsupporting
confidence: 78%
“…Introduction of the G1899A mutation overcomes the replication defect of these mutants. The G1862T mutation is frequently associated with a G1888A or G1899A covariation (8,14,25,27,33). While the G1888A mutation is silent at the amino acid level, the G1899A mutation induces a pcG29D substitution in the terminal residue of the precore peptide (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV/C has a higher G1762T/G1764A double mutation rate and a lower G1896A mutation rate than does HBV/B (26). A subgenotype of HBV/A, HBV/Aa (17,35), which is distributed in Asia and Africa, has subgenotype-specific substitutions just prior to precore ORF start codons (Kozak sequences), and the mutation causes reduction of HBeAg (2,38).…”
Section: Discussionmentioning
confidence: 99%
“…HBV subgenotype A1 appears to be associated with low serum HBV DNA levels as well as a low prevalence of serum HBeAg and is implicated in the high incidence of HBV-related HCC in Africa [61]; whereas subgenotype A2 has a higher rate of sustained remission after HBeAg seroconversion and a lower rate of liver-related death than other genotypes during long-term follow-up [62,63]. Sugauchi et al found that positivity of HBeAg is significantly more frequent in carriers of subgenotype B1 than B2 [64].…”
Section: Genotype and Subgenotypementioning
confidence: 99%